KARIKATUR POLITIK DALAM MEDIA CETAK HARIAN RAKYAT SULSEL: KAJIAN SEMIOTIK - Supriadi, Supriadi; Maknun, Tadjuddin; M. Said, Ikhwan (JURNAL ILMU BUDAYA, 2019)
This study aims to reveal the verbal and visual codes of the political caricature in the Rakyat Sulsel daily newspaper, to explain the coded iconic message and iconic message without code of political caricature in the Rakyat Sulsel daily newspaper, and to explain the function of the caricature in the Rakyat Sulsel daily newspaper. The method used in this study was the reflective qualitative method, since this method the researcher put himself as a subject and also determined the data interpretation. The result indicates that all the cartoons have different verbal codes and visual codes. Depends on the picture and message of the caricatures. Political caricature in this newspaper, not only covers four functions as forwarded by Gombrich but also there is an addition of other functions which always attach to the new cartoons such as provocative function, expressive function, social function, and interest function.